Change of Crystallographic Orientation Characteristics of (001)-Oriented Electrodeposited Silver Films During Self-Annealing at Room Temperature. (2017) - Hayashi, Yumi; Shohji, Ikuo; Koyama, Shinji; Miyazawa, Hiroshi
Abstract: Self-annealing behaviors of the electrodeposited silver films which preferentially orient in the (001) direction were investigated by in situ EBSD analysis. Self-annealing started in storage for a few hours at room temperature (R. T.) and was almost complete after storage for 6 h at R. T. In the initial stage of self-annealing, recrystallization of (001)-oriented grains progressed with the formation of twins with (212) orientation. Membrane stress in the as-electrodeposited film was compression stress of approximately 20 MPa. The compression membrane stress seems to become driving force for self-annealing of the (001)-oriented electrodeposited silver film. Membrane stress in the film changed from compression stress to tensile stress by recrystallization in self-annealing.